Management of Osteoarthritis of Knee Joint through Samana Snehapana with Sahacharadi Mezhukupaka - Case Series - Remya R G,; T K Sujan,; Manju P S,; Ambili Krishna, (International Journal of Ayurveda and Pharma Research, 2023)
Osteoarthritis is one of the oldest known chronic degenerative joint disorders characterized by joint pain, tenderness, limitation of movements, crepitus, occasional effusion and variable degrees of local inflammation. In Ayurveda, this disease clinically simulates with Sandhigata vata which occurs due to the localization of the vitiated Vata dosha in the Asthi sandhis of the body. It is characterized by the symptoms pertaining to the Asthi sandhis like Sandhi soola, Sandhi sopha etc.  Acharya Susrutha has mentioned the treatment for Sandhigata vata clearly i.e., Snehana, Upanaha, Agnikarma, Bandhana and Unmardana. In Ashtanga Hridaya, Snehana is mentioned as one of the main treatment of Sandhigata vata. Aim: To evaluate the effect of Samana snehapana with Sahacharadi mezhukupaka for a duration of 14 days in patients of OA knee joint in the age group of 40–60 years. Materials and Method: A case series of 5 patients aged between 40-60 years diagnosed as osteoarthritis of knee joint with pain, stiffness, difficulty in physical function and mobility by using WOMAC Osteoarthritis index and TUG test. They are advised to take Sahacharadi mezhukupaka for duration of 14 days after doing Rookshana with Gandharvahastadi kashyam and Vaiswanara choorna for 5 days. Assessment was done on 20th day and 35th day after treatment. Results: After completion of Snehapana for 14 days followed by assessment, there was significant relief in pain, stiffness and improvement in physical function and mobility. WOMAC Index and TUG test scores shows significant improvement in patients. Conclusion: Osteoarthritis is a muculoskeletal degenerative disease affecting the bones, cartilage, joint and connective tissue leading to the impairment of function. In Ayurveda, by using Samana snehapana patients got satisfactory relief in pain, stiffness and improvement in physical function and mobility.